2021
DOI: 10.1109/ted.2021.3049765
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ohmic Electrode on the Endurance of Oxide-Based Resistive Switching Memory

Abstract: As one of the key aspects in the reliability of redox-based resistive switching memories (ReRAMs), maximizing their endurance is of high relevance for industrial applications. The major limitation regarding endurance is considered the excessive generation of oxygen vacancies during cycling, which eventually leads to irreversible RESET failures. Thus, the endurance could be increased by using combinations of switching oxide and ohmic electrode (OE) metal that provides a high barrier for the generation of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…In other cases, we recommend optimizing the switching parameters by adaptive programming for each tested stack (or even for each device) and comparing the optimized endurance. A respective algorithm has been demonstrated …”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…In other cases, we recommend optimizing the switching parameters by adaptive programming for each tested stack (or even for each device) and comparing the optimized endurance. A respective algorithm has been demonstrated …”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…[18,24,27,32] In VCM cells, significant progress has also been made regarding the understanding of oxygen vacancy defect formation, migration [15,33] and cell switching stability. [34,35] Multiple approaches such as selecting ohmic electrode material with proper defect formation energy, [36,37] applying multilayer oxides, [21,38,39] have been attempted to improve cell performance. However, in most of the reported works, the conclusions were drawn based on studies containing only one type of variable, either the specie of active (ohmic) electrode material, or the counter (bottom) electrode material, overlooking the comprehensive analysis considering the configuration/combination of the electrode/electrolyte materials as a system.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect of the unipolar SET is that it might limit the endurance of VCM based devices. During endurance measurements on ZrO x and TaO x -based devices, with very similar device fabrication, we observed that the devices were usually trapped in the LRS [54,67], which might have been triggered by a unipolar SET event. An exemplary endurance measurement from [54], during which a ZrO x -based device got trapped in the LRS is shown in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Further information are given in the methods section. In recent publications, we have shown that devices with these material stacks have an endurance of at least 10 6 cycles [53,54]. Read operations are indicated in blue, SET operations in green and RESET operations in red.…”
Section: Reset Kineticsmentioning
confidence: 99%

Intrinsic RESET speed limit of valence change memories

von Witzleben,
Wiefels,
Kindsmüller
et al. 2021
Preprint
Self Cite